PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE TAHUN 2019-2023 - Indri Tri Damayanti; Iwin Arnova; Winny Lian Seventeen (Jurnal Ilmu Akuntansi, 2024)
This study aims to determine whether there is an effect of cash turnover and receivables turnover on profitability.  The type of data in this study is quantitative research, with secondary data sources obtained through the Annual Report. The population in this study is the Annual Report of 47 consumption companies. the sample in this study were 30 consumption companies listed on the Indonesia Stock Exchange for the period 2019-2023. the independent variable in this study is profitability, the dependent variable is cash turnover and accounts receivable turnover. The results of the research Cash turnover affects profitability and Receivables turnover affects profitability in consumer industry sector companies listed on the IDX in the 2019-2023 observation year. This can be shown from the significance value below the value of 0.05 (5%). cash turnover and accounts receivable turnover simultaneously (together) influence the profitability of consumer industry sector companies listed on the IDX in the 2019-2023 observation year. This can be shown from the value is below the value of 0.05 (5%).